Pembelajaran Baca Tulis Al-Qur'an di TPQ As-Sholih SD Negeri Tegalretna - Ismail, Fajar (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2025)
Quranic Reading and Writing Learning at As-Sholih Islamic Education Center in Tegalretna Public Elementary School There are two main objectives of this research: (1) To analyze Quranic reading and writing learning in enhancing Quranic literacy at As-Sholih Islamic Education Center in Tegalretna Public Elementary School, and (2) To analyze the supporting and hindering factors in Quranic reading and writing learning. This study adopts a qualitative approach and utilizes a case study method, with data collection through observation, interviews, and documentation. The research reveals that Quranic reading and writing learning are influenced by various aspects, including the teaching methods employed and the crucial role of teachers in developing students' abilities in reading and writing the Quran. The findings of this research indicate that As-Sholih Islamic Education Center at Tegalretna Public Elementary School represents a collaborative effort to establish Islamic-based education centered around the Quran. (1) The Quranic reading and writing learning process takes place outside regular school hours as part of extracurricular activities. Several factors affect the Quranic reading and writing learning process, including students' motivation and interest, teacher quality, facilities and resources, time, parental involvement, and the community environment. The method used at As-Sholih Islamic Education Center is the Iqro method, covering volumes 1-6. For the Quranic reading and writing classes, they are tailored to the students' basic Quranic literacy skills. (2) Tegalretna Public Elementary School plays a role in providing facilities such as students, classrooms, desks, chairs, and necessary teaching materials for As-Sholih Islamic Education Center. Since Tegalretna Public Elementary School and As-Sholih Islamic Education Center collaborate, they mutually support each other. The evaluation of As-Sholih Islamic Education Center's teaching and learning activities is conducted to observe students' progress in Quranic reading and writing skills. This evaluation takes the form of an event in which each Quranic reading and writing class will take the stage to showcase what they have learned during the academic year. Evaluation is also carried out by teachers from Tegalretna Public Elementary School and As-Sholih Islamic Education Center, although the focus and criteria for evaluation differ. The teachers' evaluation aims t discuss how to ensure the learning process continues to run smoothly.